Physics of atmospheres - Houghton, John (Cambridge, Cambridge University Press, 2002)
In the third edition of The Physics of Atmospheres, John Houghton has revised his acclaimed textbook to bring it completely up-to-date. The book provides a comprehensive concise description of the physical processes governing the structure and the circulation of the atmosphere. New chapters have been introduced on topics of strong contemporary interest such as chaos and predictability and climate change. The chapters on global observations (especially through remote sensing) and numerical modeling have also been substantially extended.
Appendix 1-10, 275-298p; Bibliographical references 301-306p.
Keywords: Atmospheric Physics; Meteorology; Astronomy